Extinction Learning in Humans: Role of the Amygdala and vmPFC - Phelps, Elizabeth A.; Delgado, Mauricio R.; Nearing, Katherine I.; LeDoux, Joseph E. (Neuron (Cambridge, Mass.), 2004)
Understanding how fears are acquired is an important step in translating basic research to the treatment of fear-related disorders. However, understanding how learned fears are diminished may be even more valuable. We explored the neural mechanisms of fear extinction in humans. Studies of extinction in nonhuman animals have focused on two interconnected brain regions: the amygdala and the ventral medial prefrontal cortex (vmPFC). Consistent with animal models suggesting that the amygdala is important for both the acquisition and extinction of conditioned fear, amygdala activation was correlated across subjects with the conditioned response in both acquisition and early extinction. Activation in the vmPFC (subgenual anterior cingulate) was primarily linked to the expression of fear learning during a delayed test of extinction, as might have been expected from studies demonstrating this region is critical for the retention of extinction. These results provide evidence that the mechanisms of extinction learning may be preserved across species.